Diseño de mezclas lattice simplex como herramienta estadística para la inclusión de harina de frijol caupí (Vigna unguiculata) en una formulación de palitos de queso - Mendoza, Juan (2022)
The cowpea bean, recognized as Cowpea (Vigna unguiculataL. Walp.), is an important crop in low-income populations due toits nutritional properties. A mixture analysis was used to obtain the formulation of dough for frozen products, type cheese sticks,including cowpea bean flour (Vigna unguiculata). The frozen sensory evaluation was carried out using an acceptance test with a 7-point hedonic scale with 91 untrained panelists of both genders of variable age between 17 and 62 years. Of the treatmentsstudied, the evaluating panel showed the greatest preference, for which the largest fraction of cowpea flour constituted it. Theaddition of cowpea flour in a higher proportion has a significant effect on the product’s nutritional and sensory properties. Cowpeaflour is indicated to partially replace wheat flour in frozen cheese sticks because it improves its flavor, color, texture, and overallimpression, providing a more nutritious product made with native raw materials.